Are medicinal plants an alternative to the use of synthetic pharmaceuticals in animal healthcare in the Brazilian semi-arid? - Silva, Jonathan Garcia; Grandi, Andrea; Caetano, Roberta de Almeida; Rodrigues, Lúcia dos Santos; Carnaúba, Amanda Ferreira; Santos, Alaide Maria Silva; Silva, Elizabete Cristina Araújo; Silva, Daniele Cristina de Oliveira Lima da; Alves, Ângelo Giuseppe Chaves; Bruschi, Piero; Bozzi, Riccardo; Silva, Henrique Costa Hermenegildo da (Ethnobotany Research and Applications, 2020)
Background: Despite the development of modern veterinary medicine, rural populations in developing countries continue to treat their animals with medicinal plants due to a combination of their low cost, easy availability, perceived efficacy and the absence of veterinary clinics. So, this study aimed to assess the consensus on the ethnobotanical knowledge from small-holders and to assess their preference either on medicinal plants or synthetic pharmaceuticals. Methods: Interviews were conducted between January and March 2015 with 30 people of both sexes, aged 24-96 years in Dom Hélder Câmara, the largest rural settlement arisen by land reform efforts with remaining Caatinga vegetation in the state of Alagoas, northeast Brazil. The following indices were calculated to help interpret the data: Smith’s Salience Index, Informant Consensus Factor (ICF) and Fidelity Level (FL). Results: Fifty-four species of plants in 45 genera and 25 botanical families were reported as treatments for 33 veterinary diseases. The highest salience value was found for Aloe vera (0.361) and Guapira graciliflora (0.336). The highest ICF values were recorded for the categories Ecto and endoparasite (0.670) and Gastrointestinal (0.630). In 76.5% of cases only the plant was used and in 23.5% of the cases synthetic pharmaceuticals were also considered as a treatment option. The highest FL values were found for G. graciliflora (84.62%) and Citrus limon (75.00%). Conclusions: Our results suggest that medicinal plants are an important alternative to synthetic remedies in this area, especially for treating helminthiasis, which cause great damage in the production of meat and derivatives. FL results may serve as the basis for prioritization of species for pharmacological studies. Key words: ethnoveterinary medicine, herbal medicine, livestock, phytotherapy, traditional knowledge.